Comparative study of Ce3+ activated chlorosulphate phosphors - Shinde, Nita; Dhoble, N S; Gedam, S C; Dhoble, S J (Recent Research in Science and Technology, 2012)
The synthesis, X-ray diffraction (XRD) and photoluminescence characteristics in chloride based halosulphate phosphors, such as KZnSO4Cl: Ce; KMgSO4Cl: Ce; have been reported in this paper. The Ce3+ emission in KMgSO4Cl: Ce phosphor is more intense than KZnSO4Cl: Ce and it may be useful for scintillation applications.